1999
DOI: 10.1385/ijgc:26:1:43
|View full text |Cite
|
Sign up to set email alerts
|

α-Fetoprotein-Producing Adenocarcinoma of the Pancreas Presenting Focal Hepatoid Differentiation

Abstract: We report a rare case of pancreatic carcinoma producing alpha-fetoprotein (AFP), showing focal hepatoid differentiation in metastatic lymph nodes. A 65-yr-old female was admitted because of abdominal pain. The serum AFP was measured at 16,170 ng/mL. Radiological examinations revealed a mass measuring 6 cm in diameter in the body and tail of the pancreas. A right supraclavicular lymphadenopathy was found and biopsied. Light microscopy showed a tumor consisting of a portion of a hepatoid area and well-differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…Review of the literature found only seven cases of hepatoid carcinoma of the pancreas, 13,[38][39][40][41] including the present case (Table 2). In six of these cases, the serum level of PIVKA-II was not measured and tissue staining for PIVKA-II was not described; however, the serum level of AFP was increased in three of four cases in which it was measured, and five of the seven cases were AFP-positive immunohistochemically.…”
Section: Discussionmentioning
confidence: 98%
“…Review of the literature found only seven cases of hepatoid carcinoma of the pancreas, 13,[38][39][40][41] including the present case (Table 2). In six of these cases, the serum level of PIVKA-II was not measured and tissue staining for PIVKA-II was not described; however, the serum level of AFP was increased in three of four cases in which it was measured, and five of the seven cases were AFP-positive immunohistochemically.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 22 adult cases reported in the literature, 10 (46%) had distant metastases at presentation, 16 (87%) underwent surgery and 9 (41%) died of the disease [2,23,28,33,34,47,48]. The mean survival rate of patients that died of disease was 18 months.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Pancreatic forms of HC are extremely uncommon, with 22 cases [2,11,19,20,23,24,25,26,28,30,33,34,43,44,45,46,47,48,49] being reported at the time of writing this review. Literature review shows divergent results in terms of survival.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations